P-219 Does artificial shrinkage prior to fresh blastocyst transfer improve ongoing pregnancy rate? A prospective double blind randomized controlled trial. (30th June 2022) - Gala, A; Ferrières-Hoa, A; Barry, F; Brouillet, S; Vintejoux, E; Gaspari, L; Anahory, T; Hamamah, S
Abstract: Study question: Does artificial shrinkage (AS) of blastocoelic cavity (BC) prior to fresh elective single blastocyst transfer (SBET) increase ongoing pregnancy rate? Summary answer: Ongoing pregnancy rates were similar with or without AS of blastocoelic cavity. AS does not seem to provide benefit before fresh blastocyst transfer. What is known already: AS of the vitrified blastocysts enhances success rate in frozen embryo transfer cycles. In vitro cultured embryos suffer changes in temperature, pH and osmotic pressure. Moreover, manipulations such as pipetting, fertilization, microscopic observations and changes of dishes can induce oxidative stress and apoptosis. The presence of cell free DNA (cfDNA) in blastocyst fluids could be the consequence of its release from dead cells. The quantity of cfDNA in blastocyst fluids could possibly be related to the rate of cell death. It is thus interesting to estimate whether AS of BC could improve the implantation rate in cycles with fresh blastocyst transfer. Study design, size, duration: Prospective, randomized, double blind controlled study. From May 20 th 2018 to June 30th 2021, 150 couples elected for fresh SBET were included in the study and were randomly selected as "AS +" group (n = 100), where AS of blastocoel was performed by laser pulse before fresh blastocyst transfer, and "AS -" group (n = 50), where fresh blastocysts were transferred without any additional intervention. Participants/materials, setting, methods: On day 5 after fertilization, one blastocyst with a grade of expansion B3, B4, B5 or B6 and type A or B quality trophectoderm (Gardner and Schoolcraft classification, 1999) was selected for transfer. After replacement, the droplet that contained the embryo from day 3 was collected for cfDNA level quantification. Ongoing pregnancy rate was determined by the visualization of a gestational sac with a foetal heartbeat 6 weeks later and cfDNA was assessed by ALU-qPCR. Main results and the role of chance: The two groups were similar for age, BMI, infertility duration and cause, stimulation characteristics and embryological parameters. The global ongoing pregnancy rate per transfer after SBET was 49.7 %. The pregnancy rate in the AS + group was slightly higher than in the control group but not significantly (respectively 50.00 % and 48, 9 %, p = 0, 91). cfDNA median value in the AS+ group was comparable to the control group (0.493 (0.219; 0.915) mg/ml and 0.595 (0.271; 1.129) mg/ml respectively (p = 0.45)). No link was found between cfDNA rate and clinical pregnancy rate. Limitations, reasons for caution: Patients included in the study are still followed to evaluate the impact of AS on live birth rate, wastage rate, obstetrical and neonatal complications. cfDNA rate was evaluated in spent culture media and not by blastocentesis, which could provide a more accurate quantification. Wider implications of the findings: To our knowledge, this is the first prospective randomized controlled study assessing the benefit of AS of BC before fresh blastocyst transfer. The inclusion of live birth rate is crucial to ascertain the interest of this technique and more studies are needed to improve the use of cfDNA in routine. Trial registration number: NCT02988544